KEANEKARAGAMAN JENIS NYAMUK Anopheles DI SEMBILAN KABUPATEN (TAHAP PRE-ELIMINASI MALARIA) DI PROVINSI SUMATERA SELATAN - Yahya Yahya; Didit Haryanto; Rahman Irpan Pahlevi; Anif Budiyanto (Vektora : Jurnal Vektor dan Reservoir Penyakit, 2020)
The province of South Sumatra is still one of the malaria endemic areas in Indonesia. The identification and mapping of malaria receptive areas have been conducted by the Provincial Health Office of South Sumatra to monitor the level of malaria receptivity in all districts/municipalities. This research was conducted in October to November 2018 in 9 districts with low malaria endemicity (Lubuklinggau City, Mura, Muratara, OKU, South OKU, East OKU, Muba, Muara Enim, and Lahat) and have not yet achieved malaria elimination. The purpose of this study was to obtain information about Anopheles mosquito species and the types of Anopheles larvae breeding habitats. Mosquito identification was carried out on adult female Anopheles mosquitoes that are captured in the vicinity of cattle pens and the results of breeding from the larval stage. The results showed that larvae and adult Anopheles were still found. Anopheles habitat types found include irrigation channels, paddy fields, paddy water flow, fish ponds, buffalo pools, swamps, and lakes. The species of Anopheles captured were Anopheles vagus, An. barbisrostris, An. tesselatus, An. subpictus, An. nigerrimus, An. kochi, An. umbrosus, An. barbumbrosus and An. maculatus. Anopheles mosquito surveillance activities must still be done regularly to prevent malaria transmission. Reactivating abandoned fish ponds and environmental management can be an alternative effort in controlling Anopheles. Abstrak Provinsi Sumatera Selatan masih termasuk salah satu wilayah endemis malaria di Indonesia. Dinas Kesehatan Provinsi Sumatera Selatan telah melakukan identifikasi dan pemetaan daerah reseptif malaria untuk memantau tingkat reseptivitas malaria di kabupaten/kota. Penelitian ini telah dilakukan pada bulan Oktober hingga November 2018 di sembilan kabupaten yang belum mencapai eliminasi malaria dan termasuk dalam endemisitas rendah (Kota Lubuklinggau, Mura, Muratara, OKU, OKU Selatan, OKU Timur, Muba, Muara Enim dan Lahat). Tujuan penelitian ini adalah untuk mendapatkan informasi mengenai spesies nyamuk Anopheles serta jenis-jenis habitat perkembangbiakan larva Anopheles. Identifikasi dilakukan pada nyamuk Anopheles betina dewasa hasil penangkapan di sekitar kandang ternak serta hasil pembiakan dari stadium larva. Hasil menunjukkan bahwa masih ditemukan larva dan Anopheles dewasa. Jenis habitat Anopheles yang ditemukan meliputi parit, sawah, aliran air pinggir sawah, kolam ikan, kubangan kerbau, kobakan, rawa, serta danau. Spesies Anopheles yang tertangkap adalah Anopheles vagus, An. barbisrostris, An. tesselatus, An. subpictus, An. nigerrimus, An. kochi, An. umbrosus, An. barbumbrosus dan An. maculatus. Kegiatan pemantauan nyamuk Anopheles secara berkala setiap bulan tetap harus dilakukan untuk mencegah terjadinya penularan malaria. Mengaktifkan kembali kolam ikan yang tidak dimanfaatkan dan manajemen lingkungan dapat menjadi upaya alternatif dalam pengendalian Anopheles.